Recombinant adeno-associated virus carrying thymosin β4 suppresses experimental colitis in mice - Zheng, Xiao-Yan; Lv, Yi-Fei; Li, Shuang; Li, Qian; Zhang, Qian-Nan; Zhang, Xue-Ting; Hao, Zhi-Ming (World journal of gastroenterology : WJG, 2017)
AIM To investigate the protective effect of a recombinant adeno-associated virus carrying thymosin β4(AAV-Tβ4) on murine colitis via intracolonic administration.METHODS AAV-Tβ4 was prepared and intracolonically used to mediate the secretory expression of Tβ4 in mouse colons. Dextran sulfate sodium(DSS) was applied to induce the murine ulcerative colitis, and 2,4,6-trinitrobenzene sulfonic acid(TNBS) was used to establish a mouse colitis model resembling Crohn’s disease. The disease severity and colon injuries were observed and graded to reveal the effects of AAV-Tβ4 on colitis. The activities of myeloperoxidase(MPO) and superoxide dismutase(SOD) and the content of malondialdehyde(MDA) were determined using biochemical assays. Colonic levels of tumor necrosis factor-α(TNF-α), interleukin(IL)-1β and IL-10 were measured using ELISA, and mucosal epithelial cell apoptosis andproliferation were detected by TUNEL assay and immunochemistry, respectively.RESULTS Recombinant AAVs efficiently delivered Lac Z and Tβ4 into the colonic tissues of the mice, and AAV-Tβ4 led to a strong expression of Tβ4 in mouse colons. In both the DSS and TNBS colitis models, AAV-Tβ4-treated mice displayed distinctly attenuated colon injuries and reduced apoptosis rate of colonic mucosal epithelia. AAV-Tβ4 significantly reduced inflammatory cell infiltrations and relieved oxidative stress in the inflamed colons of the mice, as evidenced by decreases in MPO activity and MDA content and increases in SOD activity. AAV-Tβ4 also modulated colonic TNF-α, IL-1β and IL-10 levels and suppressed the compensatory proliferation of colonic epithelial cells in DSS- and TNBS-treated mice.CONCLUSION Tβ4 exerts a protective effect on murine colitis, indicating that AAV-Tβ4 could potentially be developed into a promising agent for the therapy of inflammatory bowel diseases.